Industry as a factor in urbanization: Case study of urbanization around the petrochemical zone of Skikda - Zennir, Rabah; DERRADJI, Saif Eddine (Journal of Architecture and environment of child, 2022)
Urbanization manifests itself as a dynamic that affects the territories, causing changes in the forms of spaces and societies. The development of societies towards industry and services, particularly in the case of Algeria, has generated elements determinants, leading to the building of cities, in fact the installation of industrial platforms in a region attracts both employees and other activities that can lead to the birth of cities. The example of urbanization around the petrochemical zone created at the beginning of the seventies in Skikda clearly illustrates the above-mentioned realities, in this context this study aims to demonstrate the influence of the petrochemical zone on the urbanization, by trying to follow this process using GIS and remote sensing techniques through a multi-date approach by justifying our results by the different data collected during our reading of the work on the area and also of our survey on the field with stakeholders and citizens. This study is also part of a series of studies that we have already established in the same area, with a view to understanding the different changes and precisely the dynamics that have occurred in this area, and which are linked to industrial activity